2017
DOI: 10.1111/aogs.13154
|View full text |Cite
|
Sign up to set email alerts
|

Surgery versus conservative management of endometriomas in subfertile women. A systematic review

Abstract: Introduction. Endometriomas are present in up to 44% of all women with endometriosis and have a detrimental effect on fertility. However, it is controversial whether endometriomas should be surgically removed before assisted reproduction technology. Our purpose was to evaluate whether surgical stripping of endometriomas in subfertile women improves the chance of a live birth. Secondary outcomes were impact on ovarian reserve and pain. Material and methods. We conducted a systematic review and meta-analysis wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 36 publications
0
30
0
3
Order By: Relevance
“…First, due to its retrospective design it could have had selection bias, but it remains debatable whether the inclusion of both pathologically confirmed and unconfirmed lesions could be regarded as a pitfall. The diagnosis of endometriomas and functional hemorrhagic cysts is also based on clinical and paraclinical criteria, and an important part of these lesions is treated conservative [ 44 ]. Moreover, a previously published paper that evaluated the utility of the “T2 shading” sign [ 3 ] stated that the choice of including only histologically proven lesions produced a “greater selection bias”, decreasing the specificity of the reported findings.…”
Section: Discussionmentioning
confidence: 99%
“…First, due to its retrospective design it could have had selection bias, but it remains debatable whether the inclusion of both pathologically confirmed and unconfirmed lesions could be regarded as a pitfall. The diagnosis of endometriomas and functional hemorrhagic cysts is also based on clinical and paraclinical criteria, and an important part of these lesions is treated conservative [ 44 ]. Moreover, a previously published paper that evaluated the utility of the “T2 shading” sign [ 3 ] stated that the choice of including only histologically proven lesions produced a “greater selection bias”, decreasing the specificity of the reported findings.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical excision may increase the possibility to achieve pregnancy by restoring the anatomy of the affected ovaries in patients with endometrioma (46). However, pre-cycle surgical treatment of endometrioma does not appear to increase pregnancy rates in ART, along with a further detrimental impact on ovarian reserve (76)(77)(78)(79)(80). Considering the insufficient evidence favoring surgical excision before ART, cystectomy should only be suggested in specific situations, such as suspicious features, progressive symptoms and large cysts (87).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a meta-analysis including 28 studies investigated whether pre-ART cystectomy improved fertility, and no evidence showed any benefit of surgery, instead reporting similar CPR rates and LBR between females having undergone surgery for endometriomas and those who did not (76). Additionally, evidence from other studies demonstrated that females having undergone surgery for endometrioma before in vitro fertilization (IVF) or intracytoplasmic sperm injection exhibited similar fertility results compared with controls (77)(78)(79)(80). To the best of our knowledge, meta-analyses published to date did not detect any improvement in ART outcomes in patients undergoing cystectomy for OMA (Table I).…”
Section: Impact Of Endometrioma and Its Excision On Art Outcomesmentioning
confidence: 99%
“…Larger RCTs are lacking but may be now considered ethically questionable. In fact, according to the results of systematic literature reviews, surgical excision of small endometriomas before IVF is associated with a need for higher amounts of gonadotrophins, lower peripheral estrogens levels, reduced number of follicles, and lower number of oocytes retrieved, but no effect on the chances of pregnancy (Brink Laursen et al ., 2017; Tao et al ., 2017; Nickkho-Amiry et al ., 2018). Excision of small endometriomas before IVF is particularly discouraged in case of repetitive surgery or bilateral cysts.…”
Section: The 10 ‘Don’ts’ In Endometriosis Managementmentioning
confidence: 99%